Lack of Viral Load Within Chronic Lymphoproliferative Disorder of Natural Killer Cells: What Is Outside the Leukemic Clone? - Giussani, Edoardo; Binatti, Andrea; Calabretto, Giulia; Gasparini, Vanessa Rebecca; Teramo, Antonella; Vicenzetto, Cristina; Barilà, Gregorio; Facco, Monica; Coppe, Alessandro; Semenzato, Gianpietro; Bortoluzzi, Stefania; Zambello, Renato (Frontiers in Oncology, 2021)
Large granular lymphocyte leukemias (LGLL) are sustained by proliferating cytotoxic T cells or NK cells, as happens in Chronic Lymphoproliferative Disorder of Natural Killer cells (CLPD-NK), whose etiology is only partly understood. Different hypotheses have been proposed on the original events triggering NK cell hyperactivation and transformation, including a role of viral agents. In this perspective, we revise the lines of evidence that suggested a pathogenetic role in LGLL of the exposure to retroviruses and that identified Epstein Barr Virus (EBV) in other NK cell leukemias and lymphomas and focus on the contrasting data about the importance of viral agents in CLPD-NK. EBV was detected in aggressive NK leukemias but not in the indolent CLPD-NK, where seroreactivity against HTLV-1 retrovirus envelope BA21 protein antigens has been reported in patients, although lacking clear evidence of HTLV infection. We next present original results of whole exome sequencing data analysis that failed to identify viral sequences in CLPD-NK. We recently demonstrated that proliferating NK cells of patients harbor several somatic lesions likely contributing to sustain NK cell proliferation. Thus, we explore whether “neoantigens” similar to the BA21 antigen could be generated by aberrancies present in the leukemic clone. In light of the literature and new data, we evaluated the intriguing hypothesis that NK cell activation can be caused by retroviral agents located outside the hematopoietic compartment and on the possible mechanisms involved with the prospects of immunotherapy-based approaches to limit the growth of NK cells in CLPD-NK disease.